The Impact of Problem-Based Learning on Mathematics Education: A Systematic Literature Review - Fakhruddin, Yarits Hanifan; Nurjanah; Martadiputra, BAP (EDUTEC : Journal of Education And Technology, 2025)
This study aims to analyze the impact of the Problem-Based Learning (PBL) model on mathematics education through a Systematic Literature Review (SLR) method. The primary issue addressed is the low mathematical proficiency of Indonesian students as reflected in international standards such as PISA and TIMSS. The study identifies student abilities, learning media, educational levels, and topics best suited for PBL implementation. Data were collected from 27 articles selected using the PRISMA protocol based on inclusion criteria, such as type of literature and publication years ranging from 2020 to 2024. The findings indicate that PBL is most commonly implemented to enhance mathematical problem-solving skills. High school education (SMA) is the most frequently studied level, with topics such as geometry, algebra, and statistics being the focus. Technology-based media, such as GeoGebra, support PBL implementation by providing visualizations of abstract concepts. This study concludes that PBL significantly contributes to improving students' conceptual understanding, critical thinking, and problem-solving skills.